The United Nations and the termination of internal conflict with reference to the United Nations Organisation Mission in the Democratic Republic of the Congo : 1999-2006 - Du Plessis, Anton (University of Pretoria, 2013)
Dissertation (MSS)--University of Pretoria, 2009.